Effects of Dry Spirulina platensis and Antitranspirant on Growth and Yield of Chili Pepper (Capsicum annuum L.) - Jufri, Afifah Farida; ,, Sudradjat; Sulistyono,; Eko (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2016)
ABSTRACTChili pepper (Capsicum annuum L.) plant is very sensitive to nutrient deficiences. The alternative effective approach is trough application of bio stimulator. The objective of this research was to study the effect of Spirulina platensis dry biomass and antiranspirant on chili pepper growth and yield. This research was conducted at Dramaga District, Bogor Regency, West Java Indonesia from February to July 2014. The experiment was arranged in a factorial split plot design with three replications. The main plot was S. platensis application which consisted of two levels, i.e., without S. platensis (control) and with S. platensis application (S1). The subplot was antitranspirant which consisted of three levels of interval application, there were without antitranspirant (A0), weekly (A1) and fortnightly (A2). The results showed that application of S. platensis and antitranspirant had no significant effect on physiological responses, vegetative growth and yield components. Application of S. platensis and antitranspirant weekly on chili pepper increased marketable product by 2.1%..Keywords: S. platensis, bio stimulator, nutrient